2021
DOI: 10.3390/catal11030384
|View full text |Cite
|
Sign up to set email alerts
|

Natural Rocks–Heterogeneous Catalysts for Oil Transesterification in Biodiesel Synthesis

Abstract: Some of the more recent methods to produce biodiesel are based on heterogeneous catalysis, which has the advantage of easy separation of catalyst from the final product. In this paper, the heterogeneous transesterification of rapeseed oil with methanol is studied. The aim of this work was to investigate the possibilities of using natural catalysts in biodiesel synthesis and to determine the optimal conditions for this process. After the evaluation of catalytic effectiveness of rocks containing calcium and magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Before transesterification tests, is important to prepare the catalyst. Gaide and colleagues [15] studied dolomite as a catalyst for ester synthesis. The optimum fraction size of dolomite was obtained as 0.315-0.1 mm, and the most suitable calcination temperature was 850 • C for 4 h. For the research, snail shells were prepared under the same conditions.…”
Section: Eggshell Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Before transesterification tests, is important to prepare the catalyst. Gaide and colleagues [15] studied dolomite as a catalyst for ester synthesis. The optimum fraction size of dolomite was obtained as 0.315-0.1 mm, and the most suitable calcination temperature was 850 • C for 4 h. For the research, snail shells were prepared under the same conditions.…”
Section: Eggshell Preparationmentioning
confidence: 99%
“…Calcium oxide, both pure and in mixtures with other metals or their oxides, is used as a heterogeneous alkaline catalyst in biodiesel synthesis [13,14]. Scientists are conducting research to find calcium-rich wastes that can be used as catalysts for oil transesterification [15][16][17]. Large amounts of CaO are found in eggshells, shells of snails, molluscs, crabs, shrimps, and animal bones [18].…”
Section: Introductionmentioning
confidence: 99%
“…The observed yield trend is similar to that of methanolysis of soybean oil using hydrated lime [27], where the authors reported that no conversion was achieved at a transesterification temperature of 25°C, while FAME yields were increasing (2, 19, 57 and 100%) with higher reaction temperatures (35, 45, 55 and 60°C). Although the higher temperature is necessary for increasing the reaction rate, conducting methanolysis at temperatures well above the boiling point of alcohol results in higher energy consumption, leads to alcohol loss by evaporation [76], and can accelerate triglyceride saponification [77], which will reduce the yield of biodiesel.…”
Section: Process Conditions: Methanol:oil Volume Ratio 025 Catalyst L...mentioning
confidence: 99%
“…A type of fuel that provides high energy efficiency and boosts alternative productive chains. Biodiesel is indeed a renewable fuel that is obtained through oil transesterifications in homogeneous [5] and heterogeneous catalysis media [6]. The chemical process uses different feedstocks [7] like palm [8], Jatropha [9], algae, and palmist kernel oil [10], and reaches typical conversion efficiencies of around 99% having a high selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory policies in the use of aviation fuels establish maximum and minimum limits of partial substitution of JETA-1 in aeronautic operations [4]. These ranges allow fostering productive chains for biofuels obtained from biomass, especially in developing countries [5,6,22,23]. This is specially written in the series of compromises under the United Nations Framework Convention on Climate Change (UNFCCC) and the established guidelines by the Intergovernmental Panel on Climate Change (IPCC) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%